Salvage Therapy With Polatuzumab Vedotin, Bendamustine, and Rituximab Prior to Allogeneic Hematopoietic Transplantation in Patients With Aggressive Lymphomas Relapsing After Therapy With Chimeric Antigen Receptor T-Cells—Report on Two Cases - Gerhardt, Kristin; Jentzsch, Madlen; Georgi, Thomas; Sretenović, Aleksandra; Cross, Michael; Bach, Enrica; Monecke, Astrid; Leiblein, Sabine; Hoffmann, Sandra; Todorović, Milena; Bila, Jelena; Sabri, Osama; et al. (Frontiers in Oncology, 2021)
Up to 60% of patients with aggressive B-cell lymphoma who receive chimeric antigen receptor (CAR) T-cell therapy experience treatment failure and subsequently have a poor prognosis. Allogeneic hematopoietic stem cell transplantation (alloHSCT) remains a potentially curative approach for patients in this situation. Induction of a deep response prior to alloHSCT is crucial for long-term outcomes, but the optimal bridging strategy following relapse after CAR T-cell therapy has not yet been established. Polatuzumab vedotin, an antibody drug conjugate targeting CD79b, is a novel treatment option for use in combination with rituximab and bendamustine (Pola-BR) in relapsed or refractory disease. Patients: We report two heavily pretreated patients with primary refractory diffuse large B-cell lymphoma (DLBCL) and primary mediastinal B-cell lymphoma (PMBCL) respectively who relapsed after therapy with CAR T-cells with both nodal and extranodal manifestations of the disease. After application of three courses of Pola-BR both patients achieved a complete metabolic remission. Both patients underwent alloHSCT from a human leukocyte antigen (HLA)-mismatched donor following conditioning with busulfan and fludarabine and are disease free 362 days and 195 days after alloHSCT respectively. We conclude that Pola-BR can be an effective bridging therapy before alloHSCT of patients relapsing after CAR T-cell therapy. Further studies will be necessary to define the depth and durability of remission of this salvage regimen before alloHSCT.